Seismic Tomography and Long-Period Earthquakes Observation and Modelling at the Hengill Geothermal Volcanic Complex, Iceland - Jousset, Philippe; Haberland, Christian; Bauer, Klaus; Arnason, Knutur; Weber, Michael; Fabriol, Hubert (CCSD, 2010)
International audience Hengill volcanic complex is located at a triple-junction between two segments of the spreading ridge between North American plate and European plate, and a transform fault (South Iceland Seismic Zone). This area is subject to intense seismic activity, which is monitored continuously by a permanent seismological network, the SIL network of the Icelandic Meteorological Office. A well-developed geothermal system is exploited and the extracted vapour allows Icelanders to sustain for part of their needs in power supply and heat. In order to improve the understanding of the relationships between the seismic activity and geothermal exploitation, a network including 7 broadband seismological stations was set up from June 26th, 2006 until October 17th, 2006, in the framework of the FP6 funded IGET project. Data analysis allowed us to detect more than 600 earthquakes, amongst which long-period (LP) earthquakes were observed. We locate 339 microearthquakes with clear P- and S- arrival times and we improve the knowledge of the velocity structure by performing a joint inversion of hypocenters and 3D tomography. We find a high velocity anomaly in the area of Olkelduhàls at about 2-4 km depth and a low vP/vS ratio anomaly beneath the northern part of Mt. Hengill below 4-5 km. The northern and western limit of the detected anomalies but cannot be determined accurately by lack of coverage of the network in those areas. We compare our velocity model and resistivity anomalies obtained from electrical and TDEM surveys. The new structural features at Hengill suggest new opportunities for studying the relation between local seismicity and fluid exploitation. We find that LP observed earthquakes happen close to exploitation wells when extraction rate is changed. We model LP earthquakes using a wave propagation modelling finite difference scheme with topography, velocity model and attenuation. We find that the synthetic LP earthquake has frequencies similar to those recorded in the observed LP earthquakes. This ...